Susan Sontag: Photocritic - Netsch, Michael (Current Objectives of Postgraduate American Studies, 2012)
Susan Sontag's book On Photography“ from 1977 marks an important point in the reception of photography. In Regarding The Pain of Others“ from 2003 she revisits some of the statements she made 26 years earlier. This essay is comparing the main theses of those two works by looking at two pictures that were made on 11 September 2001 and exhibited in the Here is New York“ exhibition.